Co-education and the feminist perspective in centres of pedagogical renewal: A critical analysis - Paco Abril Morales; Alba Castellsagué (Journal of Technology and Science Education)
In the field of education, co-education has gained recognition as an approach that seeks to challenge gender stereotypes and promote egalitarian relationships. At the same time, the feminist perspective poses a profound critique of patriarchal structures and norms that perpetuate gender inequalities. The school institution has been represented in research from an ambivalent position: as a space for the reproduction of sexism and androcentrism, but also from the perspective of its transformative potential. This article proposes to analyse the intersection between co-education and the feminist perspective in the centres of pedagogical renewal, as these spaces question traditional educational models from a critical viewpoint that transcends the merely educational.